On Jointly ?-Prime (R,S)-Submodules - Yuwaningsih, Dian Ariesta; Sumaryati, Fayi Salsabila (Jurnal Matematika, Statistika dan Komputasi, 2023)
Given ? and ? be commutative ring with unity. The (?, ?)-bimodule structure has been generalized into the (?, ?)-module structure. Likewise, primeness in a module has also been generalized to the (?, ?)-module structure. However, the existing prime definition only focuses on scalar multiplication operations in modules. The ?-prime submodule is one of the generalizations of the prime submodule, which involves additive operations and scalar multiplication in the module. This article presents a generalization of the ?-prime submodules into the (?, ?)-module structure, hereinafter referred to as the jointly ?-prime (?, ?)- submodules. Furthermore, at the end of this article some properties of the jointly ?-prime (?, ?)-submodule are presented.